Complete mitochondrial genome of the brown alga Colpomenia peregrina (Scytosiphonaceae, Phaeophyceae): genome characterization and comparative analyses. (3rd May 2016) - Liu, Feng; Pang, Shaojun; Li, Jing; Li, Xia
Abstract: Colpomenia peregrina Sauvageau has a biphasic, heteromorphic life history alternated with saccate gametophytes and crustose sporophytes. The circular C. peregrina mitogenome is 36, 025 bp in length and encodes 66 genes, including 3 ribosomal RNA genes (rRNA), 25 transfer RNA genes (tRNA), 35 protein-coding genes, and 3 open reading frames (ORFs). It is the shortest and most compact of the sequenced Ectocarpales mitogenomes to date. The overall A + T content in C. peregrina mitogenome is 68.01%, higher than that of other reported Ectocarpales species (62.01–66.49%). The total intergenic spacers are 1499 bp, constituting 4.16% of the whole genome. Genome organization of C. peregrina is essentially identical to that of known Ectocarpales species, except for Pylaiella littoralis . Phylogenetic analyses based on 35 protein-coding genes show that Scytosiphon lomentaria and Petalonia fascia firstly cluster together, and then group with C. peregrina forming the Scytosiphon-Petalonia-Colpomenia subclade with high support values, indicating their close evolutionary relationships.